Perancangan Bidai Infus Untuk Anak Usia Sekolah - Putty Yunesti; Andi Rahadiyan Wijaya; I Gusti Bagus Budi Dharma; Fajar Paundra (Journal of Science and Applicative Technology, 2021)
This research designed a hand infusion splint for school-age children with an age range of 7-12 years according to the anthropometry and contours of the child's hand so that children who underwent infusion on the hand did not experience medical complications during treatment or post-hospital trauma. The method used in the design of infusion splint for school-age children is Quality Function Deployment (QFD) and House of Quality (HOQ) to get design criteria according to consumer needs, while the software used, namely SPSS and Autodesk Professional Inventor to build models. The size of the infusion splint was determined based on the hand anthropometry of school-age children. The specifications of the hand infusion splint of school-age children according to the needs of pediatric patients have a length of 189 mm, a thickness of 9 mm, and a width of 46.3 mm for arm supports, and 37.1 mm for hand supports obtained from the highest priority value in the House of Quality, namely the design of the dimensions of the splint.